India's educational scenario: A consequence of policy deficits - Bhatnagar, Deepak (2010)
Education is the lifeline of any modern day civilisation or country. India, of late has initiated certain reforms to resurrect its educational paradigm. Still, the surface view reflects a distorted image of the education sector. Undoubtedly, Indian economy has made creditable impact internationally, largely because of the contribution of Information Technology. It has been proved that the countries promoting higher education and quality research related to the actual needs reach commanding heights. Consequently for India, the permeating glitches in the educational sector at various levels, primary, secondary or higher education, need to be corrected, immediately. Of course, the attendant factors like prevailing high poverty rate, demographic pressure or social conflicts, etc., can mar the intended growth. In sum, if the country does not want to implode, the educational sector which has suffered greatly due to earlier policy lapses, should initiate pragmatic policy changes to propel it to the desired plane. - Reproduced.
Keywords: India - Educational policy; Educational policy